Electrocautery Needling and the 308-nm Excimer Lamp: A Synergistic Combination for the Treatment of Stable Non-segmental Vitiligo - Lili Yang; Pui Mun Wong; Lingli Yang; Ichiro Katayama; Huali Wu; Huimin Zhang (Adis, Springer Healthcare, 2020)
Abstract Introduction Vitiligo is an acquired chronic depigmentation disorder caused by the destruction of melanocytes. Although various treatments have been proposed for the management of vitiligo, achieving repigmentation and preventing relapse remains challenging. The aim of the study was to evaluate the effectiveness of electrocautery needling (EC needling) as a treatment for stable non-segmental vitiligo and to determine if the effectiveness of this treatment could be enhanced by combining it with the 308-nm excimer lamp (excimer lamp). Methods Thirty patients with stable non-segmental vitiligo were enrolled in this self-controlled, non-blinded study. Three vitiligo lesions of similar size, location and disease duration were selected from each patient and randomly assigned to one of three groups treated weekly with EC needling, an excimer lamp or a combination of both (combination group), respectively. The effectiveness of treatment on the repigmentation percentage and the number of treatments required for initial pigmentation were assessed. Results There was no significant difference in the repigmentation percentage between the EC needling group and the excimer lamp group (P = 0.789). The mean number of treatments required for initial repigmentation was lower in the EC needling group than in the excimer lamp group (P = 0.049). The repigmentation percentage was significantly higher in the combination group than in the EC needling group (P = 0.027) and excimer lamp group (P = 0.005). Evidence of initial pigmentation was obtained earlier in lesions treated with the combination therapy than in lesions treated with excimer lamp therapy alone (P = 0.019). Vitiligo lesions on the face and neck regions showed the highest repigmentation percentage among all anatomical regions, whereas lesions on the hands and feet showed the worst treatment response. Conclusion Electrocautery needling monotherapy was effective in treating vitiligo, and its efficacy was enhanced when combined with the 308-nm excimer lamp. This combined approach to treat vitiligo is safe and helps increase patient compliance.